Influencia de la proporción de harina de arracacha (arracacia xanthorrhiza) y de harina de trigo ( triticum aestivum) sobre las propiedades fisicoquímicas y nutricionales de las galletas para consumo humano. - Aliaga Escalante, Mario Gustavo (2011)
To diversify the use of arracacha (Arracacia xanthorrhiza), its potential was evaluated in the preparation of a biscuit made from flour arracacha, from a flour made of wheat with ratios of 2%, 7%, 11% and 50% arracacha flour. The methodology allowed to determine the physical characteristics cookie (pH), proximal chemical composition (moisture, ash, fat, fiber, protein and carbohydrates) and commercial storage stability for a month. The results showed that the composite flour, contributed to a slight increase in fiber fractions and ash on crackers. Meanwhile, the functional properties of the mixture to make cookies indicated proper interaction of the ingredients in the preparation of the proportions of 2%, 7% and 11%; however at higher ratios such as 15%, 30% and 50% could not form the dough due to the high capacity of water absorption and low plasticity flour arracacha property is emphasized to increase its proportion, that we It leads to the conclusion that arracacha has a large capacity of water absorption, a low oil absorption capacity in the dough, causing changes in the texture of the baked cookie when compared to wheat cracker. Shelf, the physicochemical characteristics of cookies, coinciding with the specifications of the Sanitary Standard for Manufacturing, Processing and Sale of Bakery Products, Biscuits and Confectionery remained R.M. No. 1020-2010 / Ministry of Health / Ministry of Health, this being attributed to the low moisture content and ash. Regarding his lifetime, it was concluded to be stored in polyethylene bags in vacuum to prevent absorption of water environmental main cause of the growth of microorganisms. Cookie made of 2%, 7% and 11% flour arracacha was a suitable ingredient in the production of biscuits with high preference sensory, constituting an alternative power source.